Un-muddying the waters: Using benthic and shorebird population data to assess intertidal mudflat conditions and inform management strategies in two Irish Sea marine protected areas - Constance M. Schéré; Terence P. Dawson; Kate Schreckenberg (Ecological Indicators, 2023)
Intertidal mudflats are highly productive coastal habitats, serving as a transition zone between terrestrial and marine ecosystems and providing a wealth of ecosystem services, including providing nursery and feeding grounds for many species of conservation and commercial importance. These habitats are important for wintering shorebirds and waders, which depend on them for food, nesting, and migration. Their importance was formally recognised in 1971 following the Ramsar Convention on Wetlands of International Importance, yet their conservation status remains largely uncertain as they are difficult to survey, and a complete understanding of their complex biophysical processes has yet to be established. While intertidal mudflats are found all around the UK coastline, there are few routine field surveys of these habitats, making effective conservation in the face of rising anthropogenic and climate pressures challenging. Marine protected areas (MPAs) across the UK list mudflats and sandflats not covered by seawater at low tide as a designation feature separate from saltmarshes, but they are often managed together – where management exists. A lack of resources has resulted in several paper parks around the UK, where MPAs are designated but not adequately monitored or managed. This study explores the use of population data of benthic species and shorebirds as a proxy for temporal changes in mudflat conditions, focusing on two MPAs in the Irish Sea, Strangford Lough in Northern Ireland, and the Solway Firth in Scotland/England. It finds that the two methods together can provide information useful to support MPA management, but this approach is hampered by poor availability of sufficient data. Such data limitation can impact what it means to achieve or maintain favourable conditions for these habitats.